Accuracy and Repeatability of the Gait Analysis by the WalkinSense System. (20th February 2014) - Castro, Marcelo P. de; Meucci, Marco; Soares, Denise P.; Fonseca, Pedro; Borgonovo-Santos, Márcio; Sousa, Filipa; Machado, Leandro; Vilas-Boas, João Paulo
Abstract : WalkinSense is a new device designed to monitor walking. The aim of this study was to measure the accuracy and repeatability of the gait analysis performed by the WalkinSense system. Descriptions of values recorded by WalkinSense depicting typical gait in adults are also presented. A bench experiment using the Trublu calibration device was conducted to statically test the WalkinSense. Following this, a dynamic test was carried out overlapping the WalkinSense and the Pedar insoles in 40 healthy participants during walking. Pressure peak, pressure peak time, pressure-time integral, and mean pressure at eight-foot regions were calculated. In the bench experiments, the repeatability (i) among the WalkinSense sensors (within), (ii) between two WalkinSense devices, and (iii) between the WalkinSense and the Trublu devices was excellent. In the dynamic tests, the repeatability of the WalkinSense (i) between stances in the same trial (within-trial) and (ii) between trials was also excellent (ICC > 0.90). When the eight-foot regions were analyzed separately, the within-trial and between-trials repeatability was good-to-excellent in 88% (ICC > 0.80) of the data and fair in 11%. In short, the data suggest that the WalkinSense has good-to-excellent levels of accuracy and repeatability for plantar pressure variables.